Równa reprezentacja kobiet w mediach? Obecność polityczek w programach publicystycznych TVP – doniesienie wstępne - Hulewska, Aleksandra (Polityka i Społeczeństwo, 2020)
One of the key objectives of European Union policy is to equalize the opportunities for women and men in the most important areas of social life. An urgent field for such actions is the solicitude of equal representation of women and men in the media (as follows from numerous studies, the mass media can strengthen or weaken gender stereotypes). Primarily the public media should obey the so-called gender mainstreaming principle – because of the public mission. Therefore the purpose of the presented study was an attempt to determine whether, in the selected TVP journalistic programs with politicians’ participation, women were sufficiently represented. Given that, according to the Quota Act, the electoral lists for the Sejm cannot be less than 35% women candidates, it was expected that there would be at least the same proportion of women and men in the analyzed material. The quantitative content analysis method was used to solve the research problem. The results showed that the representation of women in the analyzed programs was lower than originally assumed. There are therefore grounds for continuing research on the issue of women’s access to the media, especially on determinants, manifestations and socio-cultural consequences of possible gender inequalities in this area.